Pengaruh Profitabilitas dan Struktur Aset terhadap Struktur Modal: Studi Perusahaan Manufaktur Terdaftar di BEI Tahun 2018-2021 - Tiara Shasabillah Geofanny; Halkadri Fitra (Universitas Negeri Padang, 2024)
The purpose of the research is to obtain empirical evidence about the influence of profitability and asset structure on capital structure in manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2021. By using purposive sampling method, there were 61 companies as the research sample. The research uses secondary data with a quantitative approach throught causative research. The data in this research were sourced from company annual reports obtained from the website of the Indonesia Stock Exchange and the website of each company that was sampled. This research uses panel data regression analysis using Eviews12. Based on the tests carried out, the results of this research show that profitabilityhas no significant effect on capital structure, and asset structure has a significant effect on capital structure.